Reconceptualizing Marital Seizure as a Gendered Safeguard in Indonesia’s Religious Courts - Thamer Hamdi M. Almutairi; JM. Muslimin; Siebel R. Mayuk; Al Fiqri Ardiansyah; Nabilah Yusof (Mawaddah: Jurnal Hukum Keluarga Islam, 2026)
The protection of women’s economic rights in marital property disputes within Indonesia’s Religious Courts remains problematic, particularly due to the risk of asset dissipation during divorce proceedings and the limitations of procedural safeguards. This study examines the interpretation and application of marital seizure (sita marital) as a legal mechanism to secure women’s property rights, while also identifying disparities in judicial decision-making. Employing a qualitative socio-legal approach, this research analyzes 42 court decisions issued between 2018 and 2023, sourced from the Indonesian Supreme Court database. Data were analyzed through qualitative content analysis focusing on judicial reasoning, evidentiary standards, and gender-related considerations. The findings reveal three dominant judicial patterns: approval, rejection, and partial approval of marital seizure requests. These variations are largely influenced by inconsistent evidentiary thresholds and the broad scope of judicial discretion. Although a small number of decisions demonstrate gender-sensitive reasoning aligned with feminist legal theory and maqāṣid al-sharīʿa (ḥifẓ al-māl), most rulings remain procedurally formalistic, which tends to disadvantage women, particularly those lacking access to financial documentation. This study argues that marital seizure constitutes a potentially effective yet inconsistently applied procedural safeguard. It reconceptualizes marital seizure as a gender-responsive legal instrument and underscores the urgency of doctrinal reform, the establishment of standardized evidentiary guidelines, and the integration of gender-sensitive judicial approaches. These measures are essential to ensuring substantive equality and strengthening the protection of women’s economic rights in marital property disputes.